The nymph of Anacroneuria debilis (Pictet, 1841) (Plecoptera: Perlidae) - Da Silva, Fernanda Avelino Capistrano; Barbosa, Leandro Silva; de Almeida, Gisele Luziane (Zootaxa, 2011)
The nymph of Anacroneuria debilis (Pictet, 1841) is described, being the first immature of this genus described in Brazil. It can be distinguished from other described Anacroneuria nymphs by: (1) the presences of a row of fine, long bristles along the tibia; (2) by the absence of long bristles on the frons; (3) due to its distinctive color pattern; and (4) by the presences of rows of bristles on the basal third of the cercus.